2011
DOI: 10.1177/1087054711416310
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a General Factor Model of ADHD in Adults

Abstract: These results suggest a unitary component to ADHD symptoms as well as dimensional specific factors. The replication of a general factor in adults suggests continuity of symptom presentation from childhood into adulthood. Clinical implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
75
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 42 publications
18
75
0
1
Order By: Relevance
“…First, we were able to replicate the findings of previous studies by showing that a bifactor model provides a better fit to the data from both perspectives than correlated factor models, with a strong general factor and weak specific factors [4,5,6,7,8,9,10,11]. We strongly believe that this implicates that a dimensional diagnostic approach using all items is more adequate compared to the current approaches of the DSM-5 and ICD-10 classification systems where symptoms are added up within the separate dimensions (IN and HY-IM).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…First, we were able to replicate the findings of previous studies by showing that a bifactor model provides a better fit to the data from both perspectives than correlated factor models, with a strong general factor and weak specific factors [4,5,6,7,8,9,10,11]. We strongly believe that this implicates that a dimensional diagnostic approach using all items is more adequate compared to the current approaches of the DSM-5 and ICD-10 classification systems where symptoms are added up within the separate dimensions (IN and HY-IM).…”
Section: Discussionsupporting
confidence: 67%
“…Since other studies have reported comparable inconsistencies for the HY items in bifactor models [e.g. [4,5,8,27,28]], we do not consider this finding to be limited to our samples or measurement instruments. The results rather support the criticized improper definition of the HY-IM subtype [11,29] and appear to be more in line with the developments of the DSM-5, which no longer considers (temporally stable) subtypes but rather takes into account temporal representations which may change over time.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Evidence of the superiority of the hierarchical model of ADHD over one-, two-, or three-factor non-hierarchical models has been demonstrated in general population samples of children, samples of children and adolescents with ADHD recruited from the community, and clinic-referred samples, using parent, teacher, adolescent, or clinician reports (e.g., Dumenci et al 2004;Gibbins et al 2011;Martel et al 2010a, b;Toplak et al 2009; A summary of studies on the hierarchical models of ADHD is presented in Suppl. Table 1).…”
mentioning
confidence: 99%